Almohadilla Desechable Biodegradable a ser usada en un Pañal Ecológico - Cuauhtémoc Pozos Vázquez; Patricia Blanco Padilla; Martha Ofelia Mercado González; Gustavo Abraham Velez Martínez (European Scientific Journal, ESJ, 2018)
The disposition of urban solid waste is a major problem around the world today due to the large amount of spaces it occupies and the negative effects it has on the environment. These effects include pollution, most especially when it comes in contact with terrestrial and aquatic ecosystems. One of the solid wastes that are generated in large quantities is the baby diapers. This, however, is because of its high demand for use. Plastics with which conventional disposable diapers are made can take many years to degrade. An attractive alternative to reduce its contaminating effect involves the use of reusable diapers in which the absorbent is not discarded. Nevertheless, one of the major disadvantages is that it requires a lot of washing after its use. Thus, it is time-consuming as the diapers have to be washed with water and detergents. This paper focuses on an attractive alternative of a new 100% biodegradable absorbent which was produced. This alternative can be disposed without having any significant impact on the environment. Through this way, there is a promotion of the idea of using an ecological diaper with a disposable absorbent (insert) made from natural and biodegradable materials with which it would avoid exposing babies to the chemical components of conventional disposable diapers. In addition, costs are minimized since the diaper is not completely discarded; thus, only the absorbent is removed.